Acoustic Droplet Ejection Technology and Its Application in High-Throughput RNA Interference Screening. (February 2016) - Nebane, N. Miranda; Coric, Tatjana; McKellip, Sara; Woods, LaKeisha; Sosa, Melinda; Rasmussen, Lynn; Bjornsti, Mary-Ann; White, E. Lucile
The development of acoustic droplet ejection (ADE) technology has resulted in many positive changes associated with the operations in a high-throughput screening (HTS) laboratory. Originally, this liquid transfer technology was used to simply transfer DMSO solutions of primarily compounds. With the introduction of Labcyte's Echo 555, which has aqueous dispense capability, the application of this technology has been expanded beyond its original use. This includes the transfer of many biological reagents solubilized in aqueous buffers, including siRNAs. The Echo 555 is ideal for siRNA dispensing because it is accurate at low volumes and a step-down dilution is not necessary. The potential for liquid carryover and cross-contamination is eliminated, as no tips are needed. Herein, we describe the siRNA screening platform at Southern Research's HTS Center using the ADE technology. With this technology, an siRNA library can be dispensed weeks or even months in advance of the assay itself. The protocol has been optimized to achieve assay parameters comparable to small-molecule screening parameters, and exceeding the norm reported for genomewide siRNA screens.